A Cross-Sectional Survey to Determine the Prevalence of Burnout Syndrome Among Anesthesia Providers in Zambian Hospitals. (February 2020) - Mumbwe, Mbangu C.; McIsaac, Dan; Jarman, Alison; Bould, M. Dylan
Abstract : BACKGROUND: Burnout is a psychological syndrome that results from chronic exposure to job stress. It is defined by a triad of emotional exhaustion, depersonalization, and reduced personal accomplishment. In research, mostly from high-income countries, burnout is common in health care professionals, especially in anesthesiologists. Burnout can negatively impact patient safety, the physical and mental health of the anesthetist, and institutional efficiency. However, data on burnout for anesthesia providers in low- and middle-income countries are poorly described. This study sought to determine the prevalence of burnout syndrome among all anesthesia providers (physician and nonphysician) working in Zambian hospitals and to determine which sociodemographic and occupational factors were associated with burnout. METHODS: A questionnaire was sent to all Zambian anesthesia providers working in private and public hospitals. The questionnaire assessed burnout using the Maslach Burnout Inventory Human Services Survey, a validated 22-item survey widely used to measure burnout among health professionals. Sociodemographic and occupational factors postulated to be associated with burnout were also assessed. RESULTS: Surveys were distributed to all 184 anesthesia providers in Zambia; 160 were returned. This resulted in a response rate representing 87% of all anesthesia providers in the country. Eighty-six percentage of respondents were nonphysician anesthesia providers. Burnout was present in 51.3% (95% confidence interval [CI], 43.2–59.2) of participants. Logistic regression analysis revealed that "not having the right team to carry out work to an appropriate standard" (odds ratio, 2.91, 95% CI, 1.33–6.39; P = .008), and "being a nonphysician" (odds ratio, 3.4, 95% CI, 1.25–12.34; P = .019) were significantly associated with burnout in this population. CONCLUSIONS: In a cross-sectional survey of anesthesia providers in Zambia, >50% of the respondents met the criteria for burnout. The risk was particularly high among nonphysician providers who typically work in isolated rural practice. Efforts to decrease burnout rates through policy and educational initiatives to increase the quantity and quality of training for anesthesia providers should be considered.